Pemanfaatan Berbagai Sumber Pupuk Kandang sebagai Sumber N dalam Budidaya Cabai Merah (Capsicum annum L.) di Tanah Berpasir - Prasetyo, Rendy (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2014)
The aim of the research was to examine the effects of various sources of manure as a nitrogen sources on the cultivation of red chili. The experiment was conducted using experimental methods which are arranged in Complete Randomized Design (CRD) comprised 4 treatments, namely 90 ton of cow manure per hectare, 60 ton of goat manure per hectare, 36 ton of chicken manure per hectare and standard fertilizers (1 ton NPK/hectare and 20 tons of chicken manure/hectare).The results showed that treatment of manure and standards provide similar effects to the real plant height, weight fresh fruit and fruit diameter,Â  but a significantly different effect on the weight of fresh and dry weight of plant biomass, number of fruits per plant, fruit lenght and production red chilies. Treatment of 90 tons of cow manure per hectare gave the bighest production of red chili that is 302.58 grams per plant, but did not differ significantly with treatment of 36 tons of chicken manure per hectare.